Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Makanan Dan Minuman Di Rumah Makan Teja Boga Nusa Dua Bali - Yuliana Lende; Saortua Marbun (Universitas Triatma Mulya, 2025)
This research aims to determine the analysis of marketing strategies in increasing sales at the Teja Boga Nusa Dua Bali Restaurant, making it easier for the Management of the Teja Boga Nusa Dua Bali Restaurant to determine the next steps in marketing the restaurant. This research used descriptive qualitative method with Purposive Simplifying technique by interviewing and distributing it to several respondents as Sampling. This research has 20 respondents. SWOT analysis is the data analysis used in this research. The results of this research were an IFAS value of 3.49 and an EFAS value of 3.45. So the position of Teja Boga Restaurant Nusa Dua Bali is located in quadrant II which is described as a growth position so that the right strategy and results are needed to increase food sales at Teja Boga Restaurant Nusa Dua Bali by increasing market development, market penetration and product development. From the results of this research, it can be concluded that there is a need to develop attractive strategies such as strengthening branding, maintaining quality, being more innovative in product marketing, and maintaining prices that are appropriate to the food offered.